FACTORS INFLUENCING THE COMPETITIVENESS AND QUALITY OF HIGHER EDUCATION INSTITUTIONS - Salahitdinov, Sherzod (Journal of Contemporary World Studies, 2024)
This article provides practical recommendations and suggestions on factors that influence the competitiveness and quality of higher education services, as well as the competitiveness of graduates in the labor market and the level of higher education services.